Adoção de tecnologia e eficiência da exploração leiteira no município de Leopoldina, Minas Gerais - Fernandes de Araújo, José Geraldo; Seabra Rocha, Dilson; Machado Filho, Francisco; Ribon, Miguel; Lima Thiébaut, José Tarcísio (Revista Ceres, 2025)
This study examined aspects associated with adoption and efficiency in the dairy operations of milk producers in the município (county) of Leopoldina, Minas Gerais. A comparison was made between those farmers who received assistance from the Agricultural Extension Service (EMATER-MG) and those who did not.